Representational meanings in the poster of Mahsa Amini’s death: A multimodal discourse analysis - Salahuddin, Salahuddin (LITERA, 2023)
The death of Mahsa Amini in Iran garnered international attention through protests, rallies, and online movements that spread across various regions in Iran and social media platforms. Throughout the demonstration, numerous visual representations in the form of posters were created to elicit sympathy on an international scale. This article aims to uncover the representational meanings conveyed by these posters, employing a multimodal discourse perspective as introduced by Kress and Leeuwen (2021). The posters were sourced from different Instagram accounts and recommended websites like theguradian.com and dezeen.com. The findings reveal that the analyzed posters effectively communicate representational meanings through their constituent elements, including the process, participants, and circumstances. The researcher concludes that the semiotic system employed in the posters successfully establishes a connection with the issue or event being discussed. The posters depict Iranian women as individuals who courageously resist tyranny and advocate for the freedom to express themselves. The presence of distinct actions like trimming hair, clenching fists, and joining hands among women authentically portrays the protest’s reality. Hence, in this instance, the creators of the posters have conscientiously considered the crucial components, reflecting the existing reality to convey the message to the viewers accurately. Communicating meaning or delivering a message to the audience holds significant implications for the success of garnering international community support and raising awareness about the ongoing issue. Keywords: Mahsa Amini, Multimodal Analysis, Representational Meanings